TRANSCRIBING TOURISM CULTURAL CONTENT VIDEO TO ENRICH STUDENTS’ READING MATERIALS - Hanun Nadiyah; Hermansyah Hermansyah; Dewi Kartikasari (Esteem Journal of English Education Study Programme, 2023)
The learning process requires supportive elements, such as reading materials, to be effective. Providing appropriate reading materials involves adjusting the learning environment and considering the characteristics of the students. This enables teachers to motivate and guide students in constructing their language skills. Additionally, as a resident of Palembang, it is important to learn about cultural heritage to preserve the local culture. Songket, a traditional textile originating from Palembang, is one such cultural heritage. Utilising a booklet as a medium to convey information about Songket to students can enhance teaching and learning activities. The objective of this research was to develop reading materials for students by transcribing a Songket video. The researcher employed the Research and Methodology (R&D) method, as modified by Sukmadinata (2015). Data were collected through documentation and interviews. In the limited trial phase, the results indicated that the booklet required revisions in terms of content and design. Experts provided feedback to address inaccuracies in the content and grammatical errors and suggested adding the writer's information and the institution logo to the booklet. In the wider trial phase, experts recommended including additional information about Songket in the booklet before accepting it for printing as reading material. After incorporating all the necessary changes based on the feedback received, the writer concluded that the final product was accepted as suitable reading material for students, providing concise information about Palembang's Songket tradition.